Islamic Republic of Mauritania : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
The Poverty Reduction Strategy Paper, whose implementation has now reached the second year, has been the key instrument in Mauritania's economic, social, and institutional development policy. The pursuit of policies to accelerate growth, maintain macroeconomic stability, and enhance the competitiveness of the economy have thus made it possible to attain an economic growth rate of about 3.3 percent notwithstanding an unfavorable international economic climate. Annual inflation has been contained at 4 percent.